2021
DOI: 10.1002/cptc.202000283
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Three to Tango: The Length of the Oligothiophene Chain Determines the Nature of the Long‐Lived Excited State and the Resulting Photocytotoxicity of a Ruthenium(II) Photodrug

Abstract: TLD1433 is the first Ru(II) complex to be tested as a photodynamic therapy agent in a clinical trial. In this contribution we study TLD1433 in the context of structurally‐related Ru(II)‐imidozo[4,5‐f][1,10]phenanthroline (ip) complexes appended with thiophene rings to decipher the unique photophysical properties which are associated with increasing oligothiophene chain length. Substitution of the ip ligand with ter‐ or quaterthiophene changes the nature of the long‐lived triplet state from metal‐to‐ligand char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 28 publications
4
51
0
Order By: Relevance
“…Monitoring the emission at 620 nm, a 3 MLCT lifetime of 350 ns was determined for [Ru(bpy) 2 (ipPhNH 2 )] 2+ in H 2 O (Figure 4b). Again this value is in good agreement with 3 MLCT lifetimes, for example, observed for [Ru(bpy) 3 ] 2+ and [Ru(bpy) 2 ip] 2+ [25,29] . In the Ru‐membrane, the emission signal decays bi‐exponentially with lifetimes of 90 and 750 ns (Figure 4b).…”
Section: Resultssupporting
confidence: 88%
“…Monitoring the emission at 620 nm, a 3 MLCT lifetime of 350 ns was determined for [Ru(bpy) 2 (ipPhNH 2 )] 2+ in H 2 O (Figure 4b). Again this value is in good agreement with 3 MLCT lifetimes, for example, observed for [Ru(bpy) 3 ] 2+ and [Ru(bpy) 2 ip] 2+ [25,29] . In the Ru‐membrane, the emission signal decays bi‐exponentially with lifetimes of 90 and 750 ns (Figure 4b).…”
Section: Resultssupporting
confidence: 88%
“…The UV−vis absorption and emission spectra were reported previously. 29 The ratio of the rR band intensity at 1450 cm −1 (due to bpy) relative to that at 1320 cm −1 (due to the thienyl rings) is indicated by the red circles and shows the increased contribution of the thienyl vibration with increasing n for Ru-ip-0T-4T with 476 nm excitation. (c) rR spectra (normalized to the bpy band at 1320 cm −1 ) of Ru-ip-0T-4T in water with 476 nm excitation.…”
Section: Samplesmentioning
confidence: 99%
“…We highlight the primary photoinduced processes leading to the population of the photobiologically relevant long-lived triplet states that were detailed in a previous study, where it was shown that the singlet oxygen quantum yields increase (and emission quantum yields decrease) with the length of the thiophene chain. 29 Here, we explore the Ru-ip-nT (n = 0−4) series and show the impact of the initial excitation wavelength on the excited-state relaxation pathway and the population of the long-lived excited states. 29…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, transient absorption (tA) spectroscopy revealed three lifetimes of 600 ns and 1500 ns as well as a long lifetime of 8 μs for RuipPer in acetonitrile solution under inert conditions (Figure 5), which is similar to other multichromophoric Ru II complexes. [32,38,72] The transient absorption spectrum of RuipPer has two excited state absorptions (ESA between 360 and 380 nm as well as at 450 nm; Figure 5). In addition, two ground state bleaches (GSB) until 440 and 500 nm can be seen.…”
Section: Time-resolved Spectroscopymentioning
confidence: 99%